Concept for Digital Transformation of Accounting Services in Digital Conditions - Kavaldzhieva, Kalina (Research Papers, 2022)
The rapid development of information and communication technologies is defined as a leading factor in building a competitive industrial environment in the coming years. Globally and in Europe, the application of these technologies has been identified as a strategic priority for other countries. The current concept for digital transformation of accounting services is to create preconditions for further automation of this activity and conditions for competitive development of industrial companies. The need for this concept is dictated primarily by the rapid growth of new information technologies, leading to the digitization of production and business processes, as well as the creation of quality new prerequisites for generating new value. It also means preparation for building new, institutional and organizational relationships in society. This is key to managing this complex information, technology, economic and social process, including of accounting services in the context of the transformation and digitalization of industrial activities. An integrated approach to the problem analysis is applicable for reaching the objectives.
Keywords: Information base; Digitization; Accounting